Ovarian Cancer and BRCA1/2 Testing: Opportunities to Improve Clinical Care and Disease Prevention - Karakasis, Katherine; Burnier, Julia V.; Bowering, Valerie; Oza, Amit M.; Lheureux, Stephanie (Frontiers in Oncology, 2016)
Without prevention or screening options available, ovarian cancer is the most lethal malignancy of the female reproductive tract. High grade serous ovarian cancer (HGSOC) is the most common histologic subtype, and the role of germline BRCA1/2 mutation in predisposition and prognosis is established. Given the targeted treatment opportunities with PARP inhibitors, a predictive role for BRCA1/2 mutation has emerged. Despite recommendations to provide BRCA1/2 testing to all women with histologically confirmed HGSOC, uniform implementation remains challenging. The opportunity to review and revise genetic screening and testing practices will identify opportunities where universal adoption of BRCA1/2 mutation testing will impact and improve treatment of women with ovarian cancer. Improving education and awareness of genetic testing for women with cancer, as well as the broader general community, will help focus much needed attention on opportunities to advance prevention and screening programs in ovarian cancer. This is imperative not only for women with cancer, those at risk of developing cancer, but also for their first-degree relatives. In addition, BRCA1/2 testing may have direct implications for patients with other types of cancers, many which are now being found to have BRCA1/2 involvement.